A Cloud-Integrated Business Process Redesign Framework for Digital Transformation in Traditional SMEs - Yulyanty Chandra; Lorio Purnomo (Universitas Multimedia Nusantara, 2026)
Rapid development of digital technologies has forced small and medium sized businesses to rethink their business processes to remain competitive. Yet many traditional SMEs - particularly food and beverage - still operate in manual and fragmented ways and are thus limiting their operational effectiveness and scalability. In this study a cloud-embedded business process design framework for traditional Bakery enterprise is proposed using Suisse bakery Jakarta as case study. Core and supporting business activities were identified qualitatively through direct observation and semi structured interviews with operational stakeholders. Findings were translated into value chain analysis, use case modelling and cloud-based system architecture to align business processes with digital infrastructure. Results show that cloud computing in bakery management systems enables data interoperability, process flexibility and operational efficiency without compromising physical infrastructure dependency. This work contributes to the literature regarding digital transformation within traditional SMEs by systematically modelling business process redesign before cloud adoption providing theoretical as well as practical insights regarding SME digitalization strategies